Intestinal Microbiota in Ischemic and Hemorrhagic Stroke (Ictus, 2025)
Letter to the editor about "Intestinal Microbiota in Ischemic and Hemorrhagic Stroke" published in volume 5, issue 3 of ICTUS.
Keywords: Intestinal microbiota; Ischemic stroke; Hemorrhagic stroke